CATALYST FOR PRODUCING CARBOXYLIC ACID ESTER, PROCESS FOR PRODUCING CARBOXYLIC ACID ESTER, AND PROCESS FOR PRODUCING CATALYST FOR PRODUCING CARBOXYLIC ACID ESTER

The catalyst with optimized bulk density and particle size distribution, along with localized composite particles, addresses the outflow and fluidity issues of existing catalysts, ensuring high activity and stability in carboxylic ester production.

JP7603795B2Active Publication Date: 2024-12-20ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023508403
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2024-12-20
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Existing catalysts for producing carboxylic esters suffer from reduced conversion rates due to catalyst outflow and fluidity issues, which affect reaction performance over time.

Method used

A catalyst comprising catalytic metal particles and a carrier with specific bulk density, particle size distribution, and localized composite particles, optimized to minimize outflow and enhance activity.

Benefits of technology

The catalyst exhibits high activity while suppressing outflow, maintaining performance over long periods by optimizing bulk density, particle size distribution, and composite particle localization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603795000001
    Figure 0007603795000001
Patent Text Reader

Abstract

A catalyst for the production of a carboxylic acid ester, the catalyst comprising catalyst metal particles and a carrier that supports the catalyst metal particles. With respect to this catalyst for the production of a carboxylic acid ester, the bulk density thereof is from 0.50 g / cm3 to 1.50 g / cm3; if Dx is the particle diameter at which the cumulative frequency reaches x% in the volume-based particle size distribution of this catalyst for the production of a carboxylic acid ester, D10 / D50 ≥ 0.2 and D90 / D50 ≤ 2.5 are satisfied; and if W is the half width of the above-described particle size distribution, W / D50 ≤ 1.5 is satisfied.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for producing a carboxylic acid ester, a method for producing a carboxylic acid ester, and a method for producing a catalyst for producing a carboxylic acid ester. [Background technology]

[0002] Nickel or nickel compounds are widely used as catalysts for chemical synthesis such as oxidation reactions, reduction reactions, and hydrogenation reactions, and in recent years, various modifications and improvements of nickel-based catalysts have been made to realize catalytic oxygen oxidation reactions of alcohols. However, in the chemical industry, nickel and nickel compounds are known to be effective not only in alcohol oxidation reactions, but also in a wide range of reactions such as various oxidation reactions, reduction reactions, and hydrogenation reactions, as well as in catalysts for purifying automobile exhaust gases and photocatalysts.

[0003] For example, Patent Document 1 proposes a method for producing a carboxylate ester by using a composite particle support comprising composite particles composed of oxidized nickel and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper) and a carrier supporting the composite particles, the composite particle support having a support layer in which the composite particles are localized, as a catalyst. It is said that such a catalyst can maintain high reactivity for a long period of time.

[0004] Patent Document 2 describes spherical silica particles containing aluminum and magnesium, which have a specific surface area, pore volume, pore distribution, bulk density, abrasion resistance, average particle size, aluminum content, and magnesium content within a specified range. According to this document, it is possible to provide spherical silica particles that can be used in a wide range of applications, including catalyst supports, and have high mechanical strength, a large specific surface area, and good fluidity. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4803767 [Patent Document 2] Patent No. 4420991 Summary of the Invention [Problem to be solved by the invention]

[0006] In the production of carboxylic acid esters using the catalysts described in Patent Documents 1 and 2, improvement of catalytic activity is required, and a catalyst showing a higher conversion rate is required. As a result of repeated experiments on the production of carboxylic acid esters, the present inventors have found that when the production of carboxylic acid esters is carried out over a long period of time using the catalysts described in Patent Documents 1 and 2, the conversion rate of the raw material tends to gradually decrease. As a result of more detailed investigation into the cause, it has been found that the outflow of the catalyst from the reactor and the fluidity of the catalyst affect the conversion rate of the raw material. Note that, by increasing the amount of air blown in during the production of carboxylic acid esters, the addition rate of the raw material and the selectivity of the carboxylic acid ester can be improved, but if the catalyst is likely to flow out of the reactor, the effect of the catalyst outflow becomes more significant as the amount of air blown in increases, which may also hinder the improvement of the reaction results in this respect.

[0007] The present invention has been made in consideration of the problems associated with the above-mentioned conventional techniques, and has an object to provide a catalyst for producing a carboxylic acid ester, which exhibits high activity while suppressing catalyst outflow. [Means for solving the problem]

[0008] The inventors have investigated the bulk density and particle size distribution (D 10 / D 50 , D 90 / D 50 , and W / D 50 The inventors have found that the above problems can be solved by setting the above-mentioned range within a certain range, and have completed the present invention.

[0009] That is, the present invention includes the following aspects. [1] A catalyst for producing a carboxylic acid ester, comprising catalytic metal particles and a support supporting the catalytic metal particles, The bulk density of the catalyst for producing a carboxylic acid ester is 0.50 g / cm 3 More than 1.50g / cm 3 is as follows: The particle size at which the cumulative frequency is x% in the volume-based particle size distribution of the catalyst for producing a carboxylic acid ester is D x Then, D 10 / D 50 ≧0.2 and D 90 / D 50 ≦2.5, When the half-width of the particle size distribution is W, W / D 50 ≦1.5. [2] The catalyst for producing a carboxylic acid ester according to [1], wherein W is 100 μm or less. [3] The catalyst for producing a carboxylic acid ester according to [1] or [2], wherein the catalytic metal particles contain at least one element selected from the group consisting of nickel, cobalt, palladium, platinum, ruthenium, lead, gold, silver, and copper. [4] The catalyst for producing a carboxylic acid ester according to any one of [1] to [3], wherein the catalytic metal particles are composite particles containing oxidized nickel and / or cobalt, and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper). [5] The catalyst for use in producing a carboxylic acid ester according to [4], wherein a composition ratio of nickel or cobalt to X in the composite particle is 0.1 to 10 in terms of Ni / X atomic ratio or Co / X atomic ratio. [6] The catalyst for producing a carboxylic acid ester according to [4] or [5], wherein the composite particle contains nickel or cobalt in an oxidized state and gold. [7] The catalyst for use in the production of a carboxylic acid ester according to any one of [4] to [6], wherein the composite particles have an average particle size of 2 to 10 nm. [8] The catalyst for producing a carboxylic acid ester according to any one of [4] to [7], wherein the support layer in which the composite particles are localized is present in an area ranging from the surface of the catalyst for producing a carboxylic acid ester to 40% of an equivalent diameter of the catalyst for producing a carboxylic acid ester. [9] The catalyst for producing a carboxylic acid ester according to any one of [4] to [8], wherein the equivalent diameter is 200 μm or less, and the support layer in which the composite particles are localized is present in an area ranging from the surface of the catalyst for producing a carboxylic acid ester to 30% of the equivalent diameter of the catalyst for producing a carboxylic acid ester.

[10] The catalyst for producing a carboxylic acid ester according to any one of [4] to [9], further comprising an outer layer substantially free of composite particles outside the support layer in which the composite particles are localized, the outer layer having a thickness of 0.01 to 15 μm.

[11] The catalyst for producing a carboxylic acid ester according to any one of [4] to

[10] , wherein the composite particle has a core made of X, and the core is coated with oxidized nickel or cobalt.

[12] The catalyst for producing a carboxylic acid ester according to any one of [1] to

[11] , wherein the support contains silica and alumina.

[13] D 50 The catalyst for producing a carboxylic acid ester according to any one of [1] to

[12] , wherein the average particle size is 10 μm or more and 200 μm or less.

[14] A method for producing a carboxylic acid ester, comprising the step of reacting (a) an aldehyde with an alcohol, or (b) one or more alcohols, in the presence of the catalyst for producing a carboxylic acid ester according to any one of [1] to

[13] and oxygen.

[15] The method for producing a carboxylic acid ester according to

[14] , wherein the aldehyde is acrolein and / or methacrolein.

[16] The method for producing a carboxylic acid ester according to

[14] or

[15] , wherein the aldehyde is acrolein and / or methacrolein, and the alcohol is methanol. Effect of the Invention

[0010] According to the present invention, it is possible to provide a catalyst for producing a carboxylic acid ester, which exhibits high activity while suppressing the outflow of the catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention (hereinafter, also referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the following embodiment, and can be practiced with various modifications within the scope of the gist of the present invention.

[0012] [Catalyst for producing carboxylic acid esters] The catalyst for producing a carboxylic acid ester of the present embodiment is a catalyst for producing a carboxylic acid ester, comprising catalytic metal particles and a carrier supporting the catalytic metal particles, and the bulk density of the catalyst for producing a carboxylic acid ester is 0.5 g / cm 3 More than 1.5g / cm 3 The half-width of the volume-based particle size distribution of the catalyst for producing a carboxylic acid ester is 100 μm or less, and the particle size at which the cumulative frequency is x% in the volume-based particle size distribution of the catalyst for producing a carboxylic acid ester is defined as D x Then, D 10 / D 50 ≧0.2 and D 90 / D 50 ≦2.5, and W / D is the half-width of the volume-based particle size distribution. 50 ≦1.5. Because of being configured in this manner, the catalyst for producing a carboxylic acid ester of the present embodiment exhibits high activity while suppressing the outflow of the catalyst.

[0013] In this embodiment, the bulk density of the catalyst for producing a carboxylic acid ester is 0.50 g / cm 3 More than 1.50g / cm 3The bulk density is less than or equal to 0.70 g / cm. Although the bulk density is considered to have little relation to the problem of the decrease in catalytic activity, it is considered that adjusting the bulk density to the above range makes it easier for the catalyst to diffuse in the reactor, and increases the conversion rate of the raw material. That is, if the bulk density is smaller than the lower limit, the catalyst will flow out of the reactor during long-term operation, reducing the amount of catalyst and lowering activity, whereas if the bulk density is larger than the upper limit, the catalyst will have low circulation, reducing the opportunity for contact with the raw material and lowering activity. From this viewpoint, the bulk density of the catalyst for producing a carboxylic acid ester is 0.70 g / cm. 3 More than 1.30g / cm 3 It is preferable that the content is 0.90 g / cm or less, and more preferable that the content is 0.90 g / cm or less. 3 More than 1.20g / cm 3 The following is the result. The bulk density can be measured by the method described in the Examples below. The bulk density can be adjusted to fall within the above range, for example, by employing the preferred production conditions described below.

[0014] The particle size at which the cumulative frequency is x% in the volume-based particle size distribution of the catalyst for producing carboxylic acid esters is D. x Then, D 10 / D 50 is 0.2 or more. D 10 / D 50 is an index showing the extent to which small particles are present in the catalyst for producing a carboxylic acid ester relative to the average particle size, and the closer this value is to 1.0, the sharper the distribution on the small particle side is. 10 / D 50 By making D equal to or greater than 0.2, the fluidity of the catalyst for producing a carboxylic acid ester is increased, and high activity is exhibited. 10 / D 50 is preferably 0.3 to 0.8. D 10 / D 50 can be measured by a laser diffraction / scattering method, more specifically, by the method described in the Examples below. D 10 / D 50 can be adjusted to fall within the above-mentioned range, for example, by employing the preferred production conditions described below.

[0015] In this embodiment, D 90 / D 50 is 2.5 or more. This is an index showing the extent to which large particles are present in the catalyst for producing a carboxylic acid ester relative to the average particle size, and the closer this value is to 1.0, the sharper the distribution on the large particle side is. In this embodiment, D 90 / D 50 By making D 2.5 or more, the fluidity of the catalyst for producing a carboxylic acid ester is increased, and high activity is exhibited. 90 / D 50 is preferably 1.4 to 2.3. D 90 / D 50 can be measured by a laser diffraction / scattering method, more specifically, by the method described in the Examples below. D 90 / D 50 can be adjusted to fall within the above-mentioned range, for example, by employing the preferred production conditions described below.

[0016] When the half-width of the volume-based particle size distribution of the catalyst for producing carboxylic acid esters is W, W / D 50 is less than 1.5. 50 W / D is an index showing how much the peak half width in the particle size distribution spreads relative to the average particle size, and the smaller this value is, the sharper the distribution is. 50 By making W / D 1.5 or less, the flowability of the catalyst for producing a carboxylic acid ester is increased while suppressing the outflow of the catalyst, and high activity is achieved while suppressing the outflow of the catalyst. When there are multiple peaks in the particle size distribution, the W of the highest peak satisfies the above relationship. From the same viewpoint, W / D 50 is preferably 0.6 to 1.3. W / D 50can be measured by a laser diffraction / scattering method, more specifically, by the method described in the Examples below. W / D 50 can be adjusted to fall within the above-mentioned range, for example, by employing the preferred production conditions described below.

[0017] In this embodiment, the above W is preferably 100 μm or less. By setting the value of W to 100 μm or less, the outflow of the catalyst tends to be more suppressed. Not only the bulk density but also the half-width is thought to have little relation to the problem of the decrease in catalytic activity, but by adjusting the half-width to the above range, the outflow of the catalyst from the reactor is prevented, and the conversion rate of the raw material tends to increase accordingly. Note that it is not known yet that the particle size distribution of the catalyst causes the outflow of the catalyst from the reactor to an extent that it affects the conversion rate of the raw material, and this is a novel finding. From the same viewpoint, W is more preferably 5 μm or more and 95 μm or less, and further preferably 10 μm or more and 90 μm or less. W can be measured by a laser diffraction / scattering method, and more specifically, it can be measured by the method described in the examples below. W can be adjusted to fall within the above range, for example, by employing the preferred production conditions described below.

[0018] In this embodiment, D 50 is preferably 10 μm or more and 200 μm or less, more preferably 20 μm or more and 150 μm or less, even more preferably 40 μm or more and 100 μm or less, and even more preferably 40 μm or more and 80 μm or less. 50 By setting the content within this range, there is a tendency for a catalyst for producing a carboxylic acid ester that exhibits higher activity while further suppressing the outflow of the catalyst. D 50 can be measured by a laser diffraction / scattering method, more specifically, by the method described in the Examples below. D 50can be adjusted to fall within the above-mentioned range, for example, by employing the preferred production conditions described below.

[0019] In this embodiment, the particle size distribution of the catalyst is preferably single-peaked. A single-peaked particle size distribution means that the volume-based particle size distribution does not have any peak other than the highest peak that is 1 / 5 or more of the highest peak.

[0020] In this embodiment, the catalytic metal particles are not particularly limited as long as they have the function of catalyzing the reaction for producing a carboxylate ester, but from the viewpoint of catalytic performance, it is preferable that the catalytic metal particles contain at least one element selected from the group consisting of nickel, cobalt, palladium, platinum, ruthenium, lead, gold, silver, and copper. In addition, from the viewpoint of further catalytic performance, it is more preferable that the catalytic metal particles are composite particles containing oxidized nickel and / or cobalt and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper), and it is even more preferable that the composite particles contain oxidized nickel or cobalt and gold.

[0021] In this embodiment, the catalyst for producing a carboxylic acid ester preferably has a support layer in which the composite particles are localized. The term "support layer in which the composite particles are localized" refers to a region in which the composite particles are concentrated and supported in the support. In the catalyst for producing a carboxylic acid ester of this embodiment, the composite particles are preferably not randomly supported in the support but are selectively supported in a certain region, and this region is called a "support layer in which the composite particles are localized". In the catalyst for producing a carboxylic acid ester, if the composite particles are concentrated in a certain region compared to other parts, that region is a "support layer in which the composite particles are localized", and which region is the "support layer in which the composite particles are localized" can be grasped by the X-ray microprobe analysis method described later or a secondary electron reflection image of a high-resolution scanning electron microscope. The support layer in which the composite particles are localized is preferably present in a region from the surface of the catalyst for producing a carboxylic acid ester to 40% of the equivalent diameter of the catalyst for producing a carboxylic acid ester. When the support layer in which the composite particles are localized is present in the above-mentioned region, the influence of the diffusion rate of the reactants inside the support is reduced, and the reaction activity tends to be improved.

[0022] The catalyst for producing a carboxylate ester of this embodiment can have various sizes, with the effective thickness or particle diameter being on the order of μm to cm, and various shapes. Specific examples of the shape of the catalyst for producing a carboxylate ester include, but are not limited to, various shapes such as a sphere, an ellipse, a cylinder, a tablet, a hollow cylinder, a plate, a rod, a sheet, and a honeycomb. The shape can be appropriately changed depending on the reaction type, and, for example, but not limited to, a hollow cylinder or a honeycomb shape that has a small pressure loss is selected in a fixed bed reaction, and a spherical shape is generally selected under liquid phase slurry suspension conditions.

[0023] The term "equivalent diameter" used here refers to the diameter of a spherical particle, or in the case of an irregularly shaped particle, the diameter of a sphere having the same volume as the particle or the same surface area as the particle. The equivalent diameter is measured using a laser diffraction / scattering particle size distribution analyzer. 50 is measured and used as the equivalent diameter.

[0024] The thickness of the support layer in which the composite particles are localized is selected within an optimal range depending on the thickness of the support, the particle size, the type of reaction, and the reaction format. In general, the "equivalent diameter of the catalyst for producing a carboxylic acid ester" is the same as the "equivalent diameter of the support," so the "equivalent diameter of the catalyst for producing a carboxylic acid ester" can be determined by the equivalent diameter of the support.

[0025] On the other hand, when the equivalent diameter of the catalyst for producing carboxylic acid ester is 200 μm or less, it is preferable to support the composite particles in an area from the surface of the catalyst for producing carboxylic acid ester to 30% of the equivalent diameter of the catalyst for producing carboxylic acid ester. In particular, when used in a liquid phase reaction, the reaction rate and the diffusion rate of the reactants in the pores inside the carrier are affected, so that the particle diameter of the carrier has been designed to be small according to the reaction. In this embodiment, by making the support layer in which the composite particles are localized thin, a catalyst for producing carboxylic acid ester with high activity can be obtained without making the particle diameter of the carrier small. In this case, there is also an advantage that separation of the catalyst by sedimentation is easy, and separation can be made using a small-capacity separator. On the other hand, if the volume of the part in the catalyst for producing carboxylic acid ester where the composite particles are not supported becomes too large, the volume unnecessary for the reaction per reactor may become large, resulting in waste. Therefore, it is preferable to set the carrier particle diameter according to the form of the reaction, and set the thickness of the support layer in which the necessary composite particles are localized and the thickness of the layer in which the composite particles are not supported.

[0026] The catalyst for producing a carboxylate ester may have an outer layer that does not substantially contain composite particles outside the support layer where the composite particles are localized. The outer layer is preferably formed to a thickness of 0.01 to 15 μm from the outer surface of the support. By providing an outer layer in this range, the catalyst can be used as a catalyst that is resistant to catalyst poisons and suppresses the detachment of composite particles due to wear in reactions using reactors such as fluidized beds, bubble columns, and stirred reactors where friction of catalyst particles is a concern, or in reactions where accumulation of poisoning substances occurs. In addition, since the outer layer can be controlled to be extremely thin, a significant decrease in activity can be suppressed.

[0027] The thickness of the outer layer that does not substantially contain composite particles is selected in an optimal range depending on the reaction characteristics, carrier properties, the amount of composite particles supported, etc., and is preferably 0.01 to 15 μm, more preferably 0.1 to 10 μm, and even more preferably 0.2 to 5 μm. If the thickness of the outer layer (layer not supporting composite particles) exceeds 15 μm, the effect of improving the catalyst life when using the composite particles as a catalyst remains the same, but the catalytic activity may decrease. If the thickness of the outer layer is less than 0.01 μm, the composite particles tend to easily fall off due to wear.

[0028] In this embodiment, the term "substantially free of composite particles" means that there is substantially no peak showing a distribution of nickel and / or cobalt in an oxidation state and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper) with a relative intensity of 10% or more in an X-ray microprobe analysis method described below or a secondary electron reflection image of a high-resolution scanning electron microscope.

[0029] The oxidized nickel that can constitute the composite particles in this embodiment is preferably a nickel oxide (e.g., Ni2O, NiO, NiO2, Ni3O4, Ni2O3) formed by the combination of nickel with oxygen, or a nickel-containing composite oxide such as a nickel oxide compound or solid solution formed by the combination of nickel with X and / or one or more other metal elements and oxygen, or a mixture thereof. In addition, the oxidized cobalt that can constitute the composite particles in this embodiment is preferably a cobalt oxide (e.g., CoO, Co2O3, Co3O4) formed by the combination of cobalt with oxygen, or a composite oxide containing cobalt, such as a cobalt oxide compound or solid solution formed by the combination of cobalt with X and / or one or more other metal elements and oxygen, or a mixture thereof.

[0030] The term "nickel oxide" as used herein refers to a compound containing nickel and oxygen. Nickel oxide includes the above-mentioned Ni2O, NiO, NiO2, Ni3O4, Ni2O3, or hydrates thereof, nickel hydroperoxides containing OOH groups, nickel peroxides containing O2 groups, or mixtures thereof.

[0031] The term "composite oxide" as used herein refers to an oxide containing two or more metals. The term "composite oxide" refers to an oxide in which two or more metal oxides form a compound, and includes composite oxides in which oxoacid ions do not exist as structural units (e.g., nickel perovskite-type oxides and spinel-type oxides), but is a broader concept than composite oxides and includes all oxides in which two or more metals are composited. Oxides in which two or more metal oxides form a solid solution also fall within the category of composite oxides.

[0032] In the catalyst for producing a carboxylate ester of this embodiment, when nickel oxide and / or cobalt oxide are composited with X as described above, the inherent catalytic ability of nickel oxide and / or cobalt oxide having oxidative esterification activity is brought out, and a remarkably high catalytic performance that could not be achieved by a catalyst consisting of each single component tends to appear. This is a unique effect that appears by composite of nickel oxide and / or cobalt oxide with X, and is considered to be due to the dual function effect between the two metal components or the generation of new active species, etc., which creates a new catalytic action that is completely different from that of each single component. Furthermore, when oxidized nickel and / or oxidized cobalt and X are supported on a support in a highly dispersed state, it tends to realize revolutionary catalytic performance that cannot be obtained by conventional catalysts.

[0033] For example, when gold is selected as X and nickel oxide and gold are highly dispersed on the support, a remarkably high catalytic performance tends to be exhibited. Such a catalyst for producing carboxylic acid esters has a higher selectivity for carboxylic acid esters than a catalyst in which nickel oxide or gold is supported on a support, and the activity tends to be significantly improved at a specific Ni / Au composition ratio. The catalytic activity per metal atom is higher than that of a particle support consisting of each single component, and the expression of the catalytic function by the composite strongly depends on the supported composition of nickel and gold. This is presumed to be because there is an optimal ratio for the formation of the optimal oxidation state of nickel for the reaction. In this way, by dispersing and supporting the two components of nickel oxide and gold on the support, a remarkable composite effect that cannot be predicted from the simple phase addition of each single component tends to be exhibited.

[0034] The catalyst for producing a carboxylate ester in which gold is selected as X as described above has oxidized nickel and gold highly dispersed on the support, and both components tend to be composited at nano-size. When such a catalyst for producing a carboxylate ester is observed with a transmission electron microscope / scanning transmission electron microscope (TEM / STEM), a structure in which nearly spherical nanoparticles of 2 to 3 nm are uniformly dispersed and supported on the support is typically observed. Furthermore, when the nanoparticles are subjected to elemental analysis by energy dispersive X-ray spectroscopy (EDS), nickel and gold are typically observed to coexist in each particle, with the gold nanoparticles being observed to have nickel coated on their surfaces. In addition to nanoparticles containing nickel and gold, nickel components are also observed to be supported alone on the support. Furthermore, the state of the metals can be confirmed by subjecting the material to X-ray photoelectron spectroscopy (XPS) and powder X-ray diffraction (powder XRD). Typically, it is observed that gold exists as a crystalline metal, while nickel exists as an amorphous oxide having a valence of two. Furthermore, when ultraviolet-visible spectroscopy (UV-Vis), which can observe changes in the excited state of electrons, is used, it is typically observed that the surface plasmon absorption peak (approximately 530 nm) derived from gold nanoparticles, which is observed in single-metal gold nanoparticles, disappears due to the composite of nickel oxide and gold. This phenomenon of disappearance of the surface plasmon absorption peak has not been observed in catalysts consisting of combinations of gold and other metal oxide species (e.g., metal oxides such as chromium oxide, manganese oxide, iron oxide, cobalt oxide, copper oxide, and zinc oxide) other than nickel oxide, which had no effect on the reaction. This disappearance of the surface plasmon absorption peak is thought to be the result of hybridization of the electronic state via the contact interface between oxidized nickel and gold, that is, due to hybridization of the two types of metal chemical species. The conversion to highly oxidized nickel oxide can be confirmed by the color change of the catalyst and ultraviolet-visible spectroscopy (UV-Vis). By adding gold to nickel oxide, the nickel oxide changes color from gray-green to brownish red, and the UV spectrum shows absorption across almost the entire visible light range. The shape of the UV spectrum and the color of the catalyst are similar to those of highly oxidized nickel peroxide (NiO2) measured as a reference sample. It can thus be inferred that the addition of gold converts nickel oxide into highly oxidized nickel oxide. From the above results, it is considered that the structure of the composite particle when gold is selected as X is a gold particle having a core whose surface is coated with highly oxidized nickel oxide, and that no gold atoms are present on the surface of the composite particle.

[0035] The composite particles are preferably supported on the carrier in a highly dispersed state, more preferably in the form of fine particles or thin films, and the average particle size is preferably 2 to 10 nm, more preferably 2 to 8 nm, and even more preferably 2 to 6 nm. When the average particle size of the composite particles is within the above range, a specific active species structure consisting of nickel and / or cobalt and X is formed, and the reaction activity tends to be improved. Here, the average particle size of the composite particles in this embodiment means the number average particle size measured by a transmission electron microscope (TEM). Specifically, in an image observed by a transmission electron microscope, the parts with black contrast are composite particles, and the diameters of all the particles can be measured to calculate the number average.

[0036] The composition of nickel or cobalt and X in the composite particles is preferably in the range of 0.1 to 10, more preferably 0.2 to 8.0, and further preferably 0.3 to 6.0, as the Ni / X atomic ratio or Co / X atomic ratio. When the Ni / X atomic ratio or Co / X atomic ratio is within the above range, a specific active species structure consisting of nickel and / or cobalt and X and an oxidation state of nickel and / or cobalt optimal for the reaction are formed, and as a result, the activity and selectivity tend to be higher than when it is outside the above range.

[0037] The form of the composite particles is not particularly limited as long as it contains both nickel and / or cobalt and X, but it is preferable that the particles have a phase structure in which both components coexist and have any of the following structures: a solid solution structure in which chemical species randomly occupy crystal sites, a core-shell structure in which each chemical species is separated concentrically, an anisotropic phase separation structure in which phases are separated anisotropically, and a heterobondophilic structure in which both chemical species are adjacent to each other on the particle surface. More preferably, the composite particles have a core made of X, and the surface of the core is preferably coated with oxidized nickel and / or cobalt. The form of the composite particles is not particularly limited as long as it contains both components, and may be any shape such as spherical or hemispherical.

[0038] As an analytical method for observing the morphology of the composite particles, for example, a transmission electron microscope / scanning transmission electron microscope (TEM / STEM) is effective as described above, and by irradiating an electron beam on a nanoparticle image observed by TEM / STEM, elemental analysis in the particles and depiction of an element distribution image are possible. As shown in the examples described later, the composite particles in this embodiment have been confirmed to have a morphology in which nickel and / or cobalt and X are contained in each particle, and the surface of X is coated with nickel and / or cobalt. When the composite particles have such a morphology, the atomic ratio of nickel and / or cobalt to X varies depending on the position of the composition analysis point in the particle, and more nickel and / or cobalt is detected at the particle edge than at the particle center. Therefore, even in individual particles, the atomic ratio of nickel or cobalt to X has a range depending on the position of the analysis point, and the range is included in the range of the above-mentioned Ni / X atomic ratio or Co / X atomic ratio.

[0039] When gold, silver, or copper is selected as X, ultraviolet-visible spectroscopy (UV-Vis) is a useful means for identifying the structure. In the case of a single gold-silver-copper nanoparticle, the light electric field in the visible to near-infrared region is coupled with the surface free electrons of the metal, and thus exhibits surface plasmon absorption. For example, when visible light is irradiated onto a catalyst carrying gold particles, an absorption spectrum based on the plasmon resonance originating from the gold particles is observed at a wavelength of about 530 nm. However, in the catalyst for producing carboxylates carrying nickel oxide and gold according to this embodiment, the surface plasmon absorption disappears, so it can be considered that no gold is present on the surface of the composite particle according to this embodiment.

[0040] The solid form of nickel is not particularly limited as long as it can provide a desired activity, but is preferably an amorphous form in which no diffraction peak is observed by X-ray diffraction. By providing nickel in this form, it is presumed that the interaction with oxygen is enhanced when used as a catalyst for an oxidation reaction, and further, the bonding interface between oxidized nickel and X is increased, so that more excellent activity tends to be obtained.

[0041] In this embodiment, X is at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver and copper, and more preferably nickel, palladium, ruthenium, gold and silver.

[0042] The chemical state of X may be any of a metal, an oxide, a hydroxide, a composite compound containing X and nickel, cobalt or one or more other metal elements, or a mixture thereof, but the preferred chemical state is a metal or an oxide, more preferably a metal. The solid form of X is not particularly limited as long as it can provide a desired activity, and may be either a crystalline or amorphous form.

[0043] The term "other metal elements" used herein refers to a third component element or a metal component such as an alkali metal, an alkaline earth metal, or a rare earth metal contained in the catalyst for producing a carboxylate ester, in addition to the constituent elements of the support, nickel and / or cobalt in an oxidized state, and X, as described below.

[0044] As described above, the catalyst for producing a carboxylate ester of this embodiment exerts excellent effects by supporting oxidized nickel and / or cobalt and X on a carrier and forming composite particles composed of oxidized nickel and / or cobalt and X. In this embodiment, the term "composite particles" refers to particles containing different bimetallic species in one particle. Examples of bimetallic species other than these include bimetallic particles in which both components nickel and / or cobalt and X are metals, and metal particles in which nickel and / or cobalt form an alloy or intermetallic compound with X. However, when used as a catalyst for chemical synthesis, these tend to have lower selectivity to the target product and lower catalytic activity than the catalyst for producing a carboxylate ester of this embodiment.

[0045] The catalyst for producing a carboxylate ester of this embodiment preferably contains oxidized nickel and / or cobalt alone on a support, in addition to composite particles composed of oxidized nickel and / or cobalt and X. The presence of oxidized nickel and / or cobalt that is not composited with X further enhances the structural stability of the catalyst for producing a carboxylate ester, and suppresses the increase in pore size due to a long-term reaction and the accompanying particle growth of the composite particles. This effect becomes more pronounced when an aluminum-containing silica-based composition containing silica and alumina is used as the support, as described below.

[0046] The following describes the effect of increasing the structural stability of the catalyst for producing carboxylic acid esters and suppressing the increase in pore size due to a long-term reaction and the accompanying particle growth of composite particles by having oxidized nickel and / or cobalt present alone on the support.

[0047] As described later, in the synthesis reaction of a carboxylate ester, a compound of an alkali metal or an alkaline earth metal is added to the reaction system to maintain the pH of the reaction system at 6 to 9, more preferably at a neutral condition (e.g., pH 6.5 to 7.5), i.e., as close to pH 7 as possible, thereby making it possible to suppress the production of by-products inherent to the production reaction of a carboxylate ester, such as acetals, which are produced due to acidic substances typified by methacrylic acid or acrylic acid.

[0048] According to the study by the present inventors, when a gold particle support in which a single component of gold particles is supported on a carrier made of an aluminum-containing silica-based composition containing silica and alumina is used to carry out a long-term reaction by the above-mentioned reaction operation, the structure of the gold particle support tends to change gradually. This phenomenon is considered to be due to the fact that the support particles are repeatedly exposed locally to acid and base by the above-mentioned reaction operation, a part of the Al in the support is dissolved and precipitated, and the silica-alumina bridge structure is rearranged, causing the pore size of the support particles to expand. In addition, as the pore size expands, sintering of the gold particles occurs, and the surface area decreases, which tends to reduce the catalytic activity.

[0049] On the other hand, by having the composite particles and nickel and / or cobalt in a single oxidized state present on the carrier, the structural stability of the supported particles due to the above reaction operation is enhanced, and the expansion of the pore size and the growth of the composite particles tend to be suppressed. The reason for this is thought to be that, as described above, the oxidized nickel and / or cobalt react with the constituent elements of the carrier to generate a composite oxide containing nickel and / or cobalt, such as an oxide compound or solid solution of nickel and / or cobalt, and as a result of the nickel compound acting to stabilize the silica-alumina bridge structure, the structural change of the supported particles is thought to be greatly improved. The inventors presume that the manifestation of such a structural stabilization effect of the supported material is due to the oxidized nickel and / or cobalt present on the carrier. Therefore, when the oxidized nickel and / or cobalt contained in the composite particles are in contact with the carrier, this effect is of course obtained, and when the oxidized nickel and / or cobalt are present alone on the carrier, it is thought that an even greater stabilization effect can be obtained.

[0050] The support for the catalyst for producing a carboxylate ester of this embodiment is not particularly limited as long as it can support nickel and / or cobalt in an oxidized state and X, and any catalyst support used for conventional chemical synthesis can be used.

[0051] Examples of the carrier include various carriers such as activated carbon, silica, alumina, silica-alumina, titania, silica-titania, zirconia, magnesia, silica-magnesia, silica-alumina-magnesia, calcium carbonate, zinc oxide, zeolite, and crystalline metallosilicate. Preferred are activated carbon, silica, alumina, silica-alumina, silica-magnesia, silica-alumina-magnesia, titania, silica-titania, and zirconia, and more preferred are silica-alumina and silica-alumina-magnesia.

[0052] The support may contain one or more metal components selected from alkali metals (Li, Na, K, Rb, Cs), alkaline earth metals (Be, Mg, Ca, Sr, Ba), and rare earth metals (La, Ce, Pr). The metal components to be supported are preferably those that become oxides by calcination, such as nitrates or acetates.

[0053] The carrier is preferably made of an aluminum-containing silica-based composition containing silica and aluminum. That is, the carrier preferably contains silica and alumina. The carrier has higher water resistance than silica and higher acid resistance than alumina. In addition, the carrier has superior physical properties compared to conventional commonly used carriers, such as being harder and having higher mechanical strength than activated carbon, and can stably support the active components, nickel and / or cobalt in an oxidized state and X. As a result, the catalyst for producing a carboxylic acid ester can maintain high reactivity for a long period of time.

[0054] A catalyst for producing a carboxylic acid ester, which has a specific atomic ratio of oxidized nickel and / or cobalt to X and is supported by an aluminum-containing silica-based composition, has a large surface area suitable for use as a catalyst support when used as a catalyst for chemical synthesis, yet is physically stable with high mechanical strength, and also satisfies corrosion resistance against the liquid properties specific to the reaction.

[0055] The characteristics of the carrier made of the alumina-containing silica-based composition containing silica and alumina according to the present embodiment, which enables a significant improvement in catalyst life, will be described below. The reason why the mechanical strength and chemical stability of the carrier can be significantly improved is presumed to be as follows.

[0056] In the carrier made of the aluminum-containing silica-based composition, by adding aluminum (Al) to the uncrosslinked silica (Si-O) chain of the silica gel, a new Si-O-Al-O-Si bond is formed, and the Si-O bond is strengthened by the formation of an Al crosslinked structure without losing the inherent stability of the Si-O chain against acidic substances, and it is considered that the hydrolysis resistance stability (hereinafter also simply referred to as "water resistance") is significantly improved. In addition, when the Si-O-Al-O-Si crosslinked structure is formed, the number of Si-O uncrosslinked chains is reduced compared to the case of silica gel alone, and the mechanical strength is also increased. In other words, it is presumed that the amount of Si-O-Al-O-Si structure formed is correlated with the improvement of the mechanical strength and water resistance of the obtained silica gel.

[0057] One of the reasons why it has become possible to stably support oxidized nickel and / or cobalt and X on a support for a long period of time is that the support has significantly improved mechanical strength and chemical stability, as described above, and has superior physical properties compared to conventional supports that are commonly used. As a result, it is believed that the active components nickel and / or cobalt and X are less likely to peel off, making it possible to stably support them for a long period of time.

[0058] In the case of a commonly used carrier, for example, silica or silica-titania, gradual elution of nickel and / or cobalt components was observed in a long-term reaction. In contrast, the present inventors found that when the above carrier was used, the elution of nickel and / or cobalt components was suppressed for a long period of time. From the results of X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM / EDX), and double crystal high resolution X-ray fluorescence analysis (HRXRF), it was confirmed that when a silica or silica-titania carrier was used, the eluted nickel and / or cobalt components were nickel oxide or cobalt oxide present alone on the carrier. Since nickel oxide or cobalt oxide is a compound soluble in acid, when it is used as a catalyst for synthesizing a carboxylate ester, it is presumed that it is eluted by an acidic substance represented by methacrylic acid or acrylic acid, which is a by-product specific to this reaction.

[0059] Analysis of the chemical state of nickel and / or cobalt by double crystal high resolution X-ray fluorescence spectrometry (HRXRF) suggests that the nickel and / or cobalt in the catalyst for producing a carboxylate ester of the present embodiment is not limited to nickel oxide and / or cobalt oxide, which are single compounds, but is presumed to be a composite oxide containing nickel and / or cobalt, such as nickel and / or cobalt oxide compounds or solid solutions produced by the combination of nickel oxide and / or cobalt oxide with constituent elements of the support, or mixtures thereof.

[0060] Double crystal high resolution X-ray fluorescence spectrometry (HRXRF) has extremely high energy resolution, and the chemical state can be analyzed from the energy position (chemical shift) and shape of the spectrum obtained. In particular, in the Kα spectrum of 3d transition metal elements, changes in chemical shift and shape occur due to changes in valence and electronic state, and the chemical state can be analyzed in detail. In the catalyst for producing a carboxylate ester of this embodiment, a change occurred in the NiKα spectrum, and a chemical state of nickel different from that of nickel oxide, which is a single compound, was confirmed.

[0061] For example, nickel aluminate, which is formed from nickel oxide and alumina, is a compound that is insoluble in acid. It is presumed that the formation of such a nickel compound on the carrier significantly improved the elution of nickel components.

[0062] The preferred elemental composition of the carrier made of an aluminum-containing silica-based composition containing silica and alumina is that the amount of aluminum is in the range of 1 to 30 mol%, preferably 5 to 30 mol%, more preferably 5 to 25 mol% based on the total molar amount of silicon and aluminum. When the amount of aluminum is within the above range, acid resistance and mechanical strength tend to be good.

[0063] In addition, in the catalyst for producing a carboxylate ester according to the present embodiment, the carrier preferably further contains, in addition to silica and alumina, an oxide of at least one basic metal selected from alkali metals, alkaline earth metals, and rare earth metals, from the viewpoint of further improving mechanical strength and chemical stability. Examples of the alkali metal of the basic metal component include Li, Na, K, Rb, and Cs, examples of the alkaline earth metal include Be, Mg, Ca, Sr, and Ba, and examples of the rare earth metal include La, Ce, and Pr. Among the above, Mg is preferred as the alkaline earth metal, and it is particularly preferred that the carrier contains silica, alumina, and magnesia.

[0064] The elemental composition of the carrier containing silica, alumina, and at least one basic metal oxide selected from alkali metals, alkaline earth metals, and rare earth metals is such that the amount of aluminum is in the range of 1-30 mol%, preferably 5-30 mol%, more preferably 5-25 mol% relative to the total molar amount of silicon and aluminum. The composition ratio of the basic metal oxide and alumina is preferably 0.5-10, more preferably 0.5-5.0, and even more preferably 0.5-2.0 in terms of (alkali metal+1 / 2×alkaline earth metal+1 / 3×rare earth metal) / Al atomic ratio. When the elemental composition of silica, alumina, and basic metal oxide is within the above range, silicon, aluminum, and basic metal oxide form a specific stable bond structure, and as a result, the mechanical strength and water resistance of the carrier tend to be good.

[0065] Next, a preferred method for preparing the carrier will be described using an aluminum-containing silica-based composition containing silica and alumina as an example, but the method for preparing the carrier is not limited to the following. That is, an aluminum-containing silica-based composition is prepared by reacting a silica sol with an aluminum compound solution, and the carrier is thereby prepared.

[0066] In the above example, silica sol is used as the silica source. In this case, silica sol and an aluminum compound are mixed to obtain a mixture sol containing silica sol and an aluminum compound, and a multi-stage hydrothermal reaction is carried out at 20 to 100°C for 1 to 48 hours, followed by drying to obtain a gel, which is then fired under the temperature, time and atmosphere conditions described below, or an alkaline aqueous solution is added to the mixture sol to co-precipitate silica and an aluminum compound, and the mixture is dried and then fired under the conditions described below. In addition, the mixture sol can be pulverized as it is using a spray dryer, or the mixture sol is dried and the gel is granulated, etc., to obtain a carrier made of an aluminum-containing silica-based composition having a desired particle size.

[0067] A method for preparing a carrier containing silica, alumina, and an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals can be performed according to the above-mentioned method for preparing a carrier consisting of an aluminum-containing silica-based composition containing silica and alumina, by drying a slurry in which an alkali metal compound, an alkaline earth metal compound, and / or a rare earth metal compound is mixed with silica and aluminum components, and then calcining the slurry under conditions described below.

[0068] As the raw materials of the alkali metals, alkaline earth metals, and rare earth metals, generally commercially available compounds can be used, similar to the aluminum raw material. Water-soluble compounds are preferred, and hydroxides, carbonates, nitrates, and acetates are more preferred.

[0069] As another preparation method, a method of adsorbing a basic metal component selected from alkali metals, alkaline earth metals and rare earth metals to a carrier made of an aluminum-containing silica-based composition can be used.For example, a method using a dipping method, such as adding a carrier to a liquid in which a basic metal compound is dissolved and then drying, or a method using an impregnation method, such as impregnating a carrier with a basic compound in an amount equivalent to the pore volume and then drying, can be applied.However, when the method of adsorbing a basic metal component later, it is necessary to pay attention to carrying out the liquid drying process under mild conditions in order to highly disperse the basic metal component on the carrier.

[0070] In addition, inorganic or organic substances can be added to the mixed slurry of the above-mentioned various raw materials in order to control the properties of the slurry and to finely adjust the characteristics of the product, such as the pore structure, and the physical properties of the carrier to be obtained.

[0071] Specific examples of inorganic substances that can be used include mineral acids such as nitric acid, hydrochloric acid, and sulfuric acid, metal salts of alkali metals such as Li, Na, K, Rb, and Cs, and alkaline earth metals such as Mg, Ca, Sr, and Ba, water-soluble compounds such as ammonia and ammonium nitrate, and clay minerals that disperse in water to form a suspension.Specific examples of organic substances include polymers such as polyethylene glycol, methyl cellulose, polyvinyl alcohol, polyacrylic acid, and polyacrylamide.

[0072] The effects of adding inorganic and organic substances are various, but mainly include forming a spherical carrier, controlling the pore size and pore volume, etc. Specifically, the liquid quality of the mixed slurry is an important factor for obtaining a spherical carrier. By adjusting the viscosity and solid content concentration with inorganic or organic substances, the liquid quality can be changed to one that makes it easier to obtain a spherical carrier. In addition, the pore size and pore volume can be controlled by a multi-stage hydrothermal synthesis process of the mixed slurry described below. It is also preferable to appropriately select and use an optimal organic compound that remains inside the carrier during the forming stage and can be removed by firing and washing operations after forming.

[0073] (Method of producing a catalyst for producing carboxylic acid ester) The method for producing the catalyst for producing a carboxylic acid ester is not particularly limited. However, the method described below makes it easier to obtain a catalyst for producing a carboxylic acid ester having a bulk density within a predetermined range and a predetermined particle size distribution according to this embodiment.

[0074] A preferred method for producing a catalyst for producing a carboxylate ester according to the present embodiment includes a step I of spray-drying the mixed slurry in a dryer using a rotating disk system, a step II of calcining the spray-dried product to obtain a carrier, and a step III of supporting catalytic metal particles on the carrier. Furthermore, in the method for producing a catalyst for producing a carboxylate ester according to the present embodiment, in the step I, the feed amount of the mixed slurry to be sprayed relative to the lateral radius of the spray dryer is set to 5×10 -3 m 2 / Hr or more 70×10 -3 m 2 / Hr or less, and the peripheral speed of the disk is 10 m / s or more and 120 m / s or less. According to the above-described method, it becomes easier to obtain a bulk density and particle size distribution within a predetermined range in the catalyst for producing a carboxylate ester according to this embodiment, and a catalyst for producing a carboxylate ester that exhibits high activity while suppressing catalyst outflow can be obtained.

[0075] When preparing the mixed slurry used in step I in this embodiment, for example, the raw material mixture can be stirred while appropriately adjusting the heating conditions.

[0076] The carrier in this embodiment can be produced by spray-drying a mixed slurry containing the above-mentioned various raw materials and additives, as in steps I and II. As a method for turning the mixed slurry into droplets, a known spray device such as a rotating disk type, a two-fluid nozzle type, or a pressure nozzle type can be used.

[0077] The liquid to be sprayed (mixed slurry) is preferably used in a well-mixed state (in a state where each component is well dispersed). When the mixture is well mixed, there is a tendency to reduce adverse effects on the performance of the carrier, such as a decrease in durability caused by uneven distribution of each component. In particular, when preparing the raw material mixture, the viscosity of the slurry may increase and partial gelation (condensation of colloids) may occur, and there is a concern that non-uniform particles may be formed. Therefore, in addition to taking care to gradually mix the raw materials under stirring, it may be preferable to control the silica sol to a metastable region of pH around 2 by adding an acid or alkali.

[0078] The liquid to be sprayed (mixed slurry) preferably has a certain degree of viscosity and solid content concentration. When the viscosity and solid content concentration are above a certain level, the porous bodies obtained by spray drying tend to be prevented from becoming sunken spheres instead of perfect spheres. When the viscosity and solid content concentration are below a certain level, the dispersion of the porous bodies among themselves can be ensured, and they tend to contribute to the formation of stable droplets. Furthermore, the change in viscosity (final Δviscosity) from one hour before the start of spray drying (state of raw material mixed liquid) to spraying (state of mixed slurry) tends to affect the particle size distribution and bulk density obtained by spray drying. From the above viewpoints, the final Δviscosity is preferably less than 10 mPa·s / Hr, more preferably 7 mPa·s / Hr or less, and even more preferably 5 mPa·s / Hr or less. The lower limit of the final Δviscosity is not particularly limited, but is, for example, 0 mPa·s / Hr or more. The final Δviscosity can be measured based on the method described in the Examples below. Moreover, the solid content is preferably within a range of 10 to 50% by mass in view of the shape, bulk density, and particle size. Furthermore, the tip speed of the stirring blade when stirring the raw material mixture is not particularly limited, but from the viewpoint of controlling the final Δviscosity, it is preferably from 3 m / s to 9 m / s, more preferably from 4 m / s to 8 m / s, and even more preferably from 5 m / s to 7 m / s.

[0079] When the mixed slurry is spray-dried in a dryer using a rotating disk method, the following conditions are preferred. The rotating disk dryer is equipped with a disk such as an atomizer. The disk can spray the mixed slurry to adjust the bulk density and particle size distribution of the dried product. Specifically, the feed rate of the liquid to be sprayed relative to the lateral radius of the spray dryer is 5×10 -3 m 2 / Hr or more 70×10 -3 m 2 / Hr or less is preferable, and 10×10 -3 m 2 / Hr or more 50×10 -3 m 2 / Hr or less is preferable, and 20×10-3 m 2 / Hr or more 40×10 -3 m 2 / Hr or less is more preferable. The peripheral speed of the disk is preferably 10 m / s or more and 120 m / s or less, more preferably 20 m / s or more and 100 m / s or less, and even more preferably 30 m / s or more and 90 m / s or less.

[0080] The calcination temperature of the carrier is generally selected from the range of 200 to 800°C. Calcination at a temperature exceeding 800°C is undesirable because the specific surface area tends to decrease significantly. The calcination atmosphere is not particularly limited, but calcination is generally performed in air or nitrogen. The calcination time can be determined according to the specific surface area after calcination, but is generally 1 to 48 hours. The calcination conditions change the carrier properties such as porosity, so it is necessary to select appropriate temperature conditions and heating conditions. If the calcination temperature is too low, it tends to be difficult to maintain durability as a composite oxide, and if it is too high, there is a risk of a decrease in the pore volume. The temperature rise conditions are preferably gradually increased using a program temperature rise or the like. If calcination is performed under suddenly high temperature conditions, gasification and combustion of inorganic and organic substances become intense, and the material is exposed to a high temperature condition above the set temperature, which is undesirable because it causes pulverization. The particle size distribution can also be controlled by adding a classification step after calcination or after catalyst loading. Examples of classification devices include sieves, vibrating sieve machines, inertial classifiers, forced vortex centrifugal classifiers, and free vortex classifiers such as cyclones.

[0081] The specific surface area of ​​the support is set to 10 m as measured by the BET nitrogen adsorption method from the viewpoints of ease of supporting the composite particles, reaction activity when used as a catalyst, difficulty of detachment, and reaction activity. 2 / g or more is preferable, and 20m 2 / g or more is more preferable, and 50m 2 From the viewpoint of activity, there is no particular limitation, but from the viewpoint of mechanical strength and water resistance, it is more preferable that the content of the polymer is 700m 2 / g or less is preferable, and 350m 2 / g or less is more preferable, and 300m 2 / g or less is more preferable.

[0082] When the pore diameter of the carrier is smaller than 3 nm, the peeling property of the supported metal tends to be good, but when used as a catalyst in a liquid phase reaction or the like, the pore diameter is preferably 3 nm or more from the viewpoint of maintaining high reaction activity without increasing the diffusion resistance in the pores too much so as not to limit the diffusion process of the reaction substrate. On the other hand, from the viewpoint of the difficulty of cracking the supported material and the difficulty of peeling off the supported metal, it is preferable that it is 50 nm or less. Therefore, the pore diameter of the carrier is preferably 3 nm to 50 nm, more preferably 3 nm to 30 nm. The pore volume is necessary for the existence of pores that support composite nanoparticles. However, there is a tendency for the strength to decrease rapidly as the pore volume increases. Therefore, from the viewpoint of strength and support characteristics, the pore volume is preferably in the range of 0.1 to 1.0 mL / g, more preferably in the range of 0.1 to 0.5 mL / g. It is preferable that the carrier of this embodiment has both the pore diameter and the pore volume that satisfy the above range.

[0083] The shape of the carrier is selected depending on the reaction format, and in the case of a fixed bed, a hollow cylindrical or honeycomb shape with a structure with little pressure loss is selected, while in the case of a liquid phase slurry suspension condition, a spherical shape is generally selected with an optimal particle size selected from the reactivity and separation method. For example, when adopting a catalyst separation process by sedimentation separation, which is generally simple, a particle size of 10 to 200 μm is preferably selected from the balance with the reaction characteristics, more preferably 20 to 150 μm, and even more preferably 30 to 150 μm. In the cross filter method, small particles of 0.1 to 20 μm or less are preferred because they have higher reactivity. The type and shape can be changed according to the purpose of use and used as a catalyst for chemical synthesis.

[0084] The amount of oxidized nickel or cobalt supported on the carrier is not particularly limited, but is usually 0.01 to 20 mass%, preferably 0.1 to 10 mass%, more preferably 0.2 to 5 mass%, and even more preferably 0.5 to 2 mass% as nickel or cobalt relative to the carrier mass. The amount of X supported on the carrier is usually 0.01 to 10 mass%, preferably 0.1 to 5 mass%, more preferably 0.2 to 2 mass%, even more preferably 0.3 to 1.5 mass%, and particularly preferably 0.5 to 1.0 mass% as metal relative to the carrier mass.

[0085] Furthermore, in this embodiment, there is a suitable range for the atomic ratio of nickel and / or cobalt to the constituent elements of the support. When using a support made of an aluminum-containing silica-based composition containing silica and alumina in this embodiment, the composition ratio of nickel or cobalt to alumina in the catalyst is preferably 0.01 to 1.0, more preferably 0.02 to 0.8, and even more preferably 0.04 to 0.6, in terms of Ni / Al atomic ratio or Co / Al atomic ratio. Furthermore, when a carrier containing silica, alumina, and an oxide of at least one basic metal selected from alkali metals, alkaline earth metals, and rare earth metals is used, the composition ratio of nickel or cobalt to alumina in the support is preferably 0.01 to 1.0, more preferably 0.02 to 0.8, and even more preferably 0.04 to 0.6, in terms of Ni / Al atomic ratio or Co / Al atomic ratio, and the composition ratio of nickel or cobalt to basic metal components is preferably 0.01 to 1.2, more preferably 0.02 to 1.0, and even more preferably 0.04 to 0.6, in terms of Ni / (alkali metal+alkaline earth metal+rare earth metal) atomic ratio or Co / (alkali metal+alkaline earth metal+rare earth metal) atomic ratio.

[0086] When the atomic ratio of nickel and / or cobalt to the aluminum and basic metal oxide, which are the carrier constituent elements, is within the above range, the effect of improving the dissolution of nickel and / or cobalt and the structural change of the supported particles tends to be large. This is thought to be because nickel and / or cobalt, aluminum, and basic metal oxide form a specific composite oxide within the above range, forming a stable bond structure.

[0087] The catalyst for producing a carboxylate ester of this embodiment may contain a third component element in addition to oxidized nickel and / or cobalt and X as active components. Examples of the third component element include titanium, vanadium, chromium, manganese, iron, zinc, gallium, zirconium, niobium, molybdenum, rhodium, cadmium, indium, tin, antimony, tellurium, hafnium, tantalum, tungsten, rhenium, osmium, iridium, mercury, thallium, lead, bismuth, aluminum, boron, silicon, and phosphorus. The content of these third component elements in the support is preferably 0.01 to 20 mass%, more preferably 0.05 to 10 mass%. The catalyst for producing a carboxylate ester may also contain at least one metal component selected from alkali metals, alkaline earth metals, and rare earth metals. The content of the alkali metals, alkaline earth metals, and rare earth metals in the support is preferably selected from the range of 15 mass% or less.

[0088] The third component element or the alkali metal, alkaline earth metal, and rare earth metal may be incorporated into the support during the production or reaction of the catalyst for producing a carboxylate ester, or may be incorporated into the support in advance.

[0089] The specific surface area of ​​the catalyst for producing a carboxylic acid ester of the present embodiment is preferably 20 to 350 m as measured by the BET nitrogen adsorption method from the viewpoint of reaction activity and difficulty in releasing the active component. 2 / g, more preferably 50 to 300m 2 / g, more preferably 100 to 250 m 2 / g range.

[0090] The pore size of the catalyst for producing carboxylic acid ester is derived from the pore structure of the carrier. If the pore size is smaller than 3 nm, the peeling property of the supported metal component tends to be good. However, when the catalyst is used in a liquid phase reaction or the like, the pore size is preferably 3 nm or more from the viewpoint of maintaining high reaction activity without increasing the diffusion resistance in the pores too much so as not to limit the diffusion process of the reaction substrate. On the other hand, from the viewpoint of the difficulty of cracking the supported material and the difficulty of peeling off the supported composite particles, the pore size is preferably 50 nm or less. Therefore, the pore size of the catalyst for producing carboxylic acid ester is preferably 3 nm to 50 nm, more preferably 3 nm to 30 nm, and even more preferably 3 nm to 10 nm. From the viewpoint of the supporting characteristics and the reaction characteristics, the pore volume is preferably in the range of 0.1 to 1.0 mL / g, more preferably 0.1 to 0.5 mL / g, and even more preferably 0.1 to 0.3 mL / g. The catalyst for producing carboxylic acid ester of this embodiment is preferably one in which both the pore size and the pore volume satisfy the above ranges.

[0091] [Method of producing a catalyst for producing carboxylic acid esters] The method for producing the catalyst for producing a carboxylic acid ester according to the present embodiment is not particularly limited, but may include the following preferred steps. Each step will be described below.

[0092] In the first step, an aqueous slurry containing a carrier carrying an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals is mixed with an acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper). The temperature of the mixture of the two liquids is adjusted to 60° C. or higher. In the mixture, a precursor of a catalyst for producing a carboxylic acid ester is formed in which nickel and / or cobalt and the X component are precipitated on the carrier.

[0093] Next, in the second step, the precursor obtained in the first step is washed with water, dried, and then heat-treated to obtain a catalyst for producing a carboxylic acid ester.

[0094] According to this method, it is possible to obtain a catalyst for producing a carboxylic acid ester, which has a support layer in which the composite particles are localized, and which does not contain the composite particles in the region including the center of the support.

[0095] In this embodiment, it is preferable to carry out an aging step in which the carrier carrying at least one oxide of a basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals is aged in water prior to the first step. By aging the carrier in advance, a sharper composite particle distribution layer can be obtained. It is presumed that the effect of aging the carrier is due to the rearrangement of the carrier's pore structure, resulting in a more uniform and sharp pore structure, based on the results of pore distribution measurement by nitrogen adsorption method. The aging temperature of the carrier can be at room temperature, but since the change in the pore structure is slow, it is preferable to select from the range of 60 to 150°C, which is higher than room temperature. When performing at normal pressure, the range of 60 to 100°C is preferable. The time of the aging treatment varies depending on the temperature conditions, but for example, at 90°C, it is preferably 1 minute to 5 hours, more preferably 1 to 60 minutes, and even more preferably 1 to 30 minutes. As for the operation of the first step, after aging the support, the support can be used after drying and calcining once, but it is preferable to contact a slurry in which the support is dispersed in water with an acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X, thereby insolubilizing and immobilizing nickel and / or cobalt and the X component on the support.

[0096] Examples of soluble metal salts containing nickel used in the preparation of the catalyst include nickel nitrate, nickel acetate, nickel chloride, etc. Examples of soluble metal salts containing X include, for example, palladium chloride, palladium acetate, etc. when palladium is selected as X, ruthenium chloride, ruthenium nitrate, etc. when ruthenium is selected, chloroauric acid, sodium gold chloride, potassium dicyanoaurate, diethylamine gold trichloride, gold cyanide, etc. when gold is selected, and silver chloride, silver nitrate, etc. when silver is selected.

[0097] The concentration of each of the aqueous solutions containing nickel and / or cobalt and X is usually in the range of 0.0001 to 1.0 mol / L, preferably 0.001 to 0.5 mol / L, and more preferably 0.005 to 0.2 mol / L. The ratio of nickel or cobalt and X in the aqueous solution, expressed as the Ni / X atomic ratio or the Co / X atomic ratio, is preferably in the range of 0.1 to 10, more preferably 0.2 to 5.0, and further preferably 0.5 to 3.0.

[0098] The temperature when the support is contacted with the acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X is one of the important factors for controlling the distribution of the composite particles, and varies depending on the amount of oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals and rare earth metals pre-supported on the support, but if the temperature is too low, the reaction slows down and the distribution of the composite particles tends to spread. In the manufacturing method of this embodiment, from the viewpoint of obtaining a support layer in which sharper composite particles are localized, the temperature when the support is contacted with the acidic aqueous solution of a soluble metal salt containing nickel and / or cobalt and X is a temperature at which a high reaction rate can be obtained, and is preferably 60°C or higher, more preferably 70°C or higher, even more preferably 80°C or higher, and particularly preferably 90°C or higher. Since it is sufficient to mix so that the temperature of the mixture of the acidic aqueous solution and the water slurry is 60°C or higher, the water slurry may be heated to such an extent that the mixture exceeds 60°C even when the acidic aqueous solution is added, or conversely, only the acidic aqueous solution may be heated. Of course, both the acidic aqueous solution and the water slurry may be heated to 60° C. or higher.

[0099] The reaction can be carried out under pressure at a temperature equal to or higher than the boiling point of the solution, but is usually preferably carried out at a temperature equal to or lower than the boiling point for ease of operation. The time required for immobilizing nickel and / or cobalt and the X component is not particularly limited, and varies depending on conditions such as the type of carrier, the amount and ratio of nickel and / or cobalt and X supported, but is usually within the range of 1 minute to 5 hours, preferably 5 minutes to 3 hours, and more preferably 5 minutes to 1 hour.

[0100] The method for producing a catalyst for producing a carboxylate ester according to the present embodiment is based on the principle of insoluble immobilization of nickel and / or cobalt and the X component by a chemical reaction between an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals, which is preliminarily supported on a support, and a soluble metal salt containing nickel and / or cobalt and X. In order to more fully composite nickel and / or cobalt with the X component, it is preferable to simultaneously immobilize them from a mixed aqueous solution of both components.

[0101] In addition, in the production method of this embodiment, the aqueous slurry containing a support carrying an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals preferably contains at least one basic metal salt selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals.

[0102] This makes it possible to suppress the generation of black metal of X, promote the composite of nickel and / or cobalt with X, and furthermore, to more precisely control the distribution of the composite particles. It is presumed that such effects are due to the fact that the addition of at least one metal salt selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals to the aqueous solution controls the rate of chemical reaction between the basic metal oxide pre-supported on the carrier, nickel and / or cobalt, and the soluble metal salt containing X.

[0103] As the at least one basic metal salt selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals, one or more selected from water-soluble salts such as inorganic salts, such as organic acid salts, nitrates, and chlorides of these metals can be used.

[0104] The amount of at least one basic metal salt selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals varies depending on the amount and ratio of nickel and / or cobalt and the X component, and is determined by the amount of basic metal oxide preliminarily supported on the support. It is usually 0.001 to 2 times by mol, preferably 0.005 to 1 times by mol, based on the amount of nickel and / or cobalt and the X component in the aqueous solution.

[0105] In addition, the aqueous slurry containing a support carrying an oxide of at least one basic metal selected from the group consisting of alkali metals, alkaline earth metals, and rare earth metals preferably contains a soluble aluminum salt, such as aluminum chloride or aluminum nitrate.

[0106] By adding a soluble aluminum salt to the water slurry, an outer layer that is substantially free of composite particles can be formed outside the support layer in which the composite particles are localized. This is also based on the above-mentioned principle of insoluble immobilization. As the soluble aluminum salt, soluble salts such as aluminum chloride and aluminum nitrate are used, and aluminum reacts with the basic metal oxide pre-supported on the support by chemical reaction, consuming the reaction field of nickel and / or cobalt with X, and further immobilizing the basic metal oxide, nickel and / or cobalt, and X component inside by reaction.

[0107] The amount of the aluminum component varies depending on the thickness of the layer not carrying nickel and / or cobalt and the X component, and is determined by the amount of the basic metal oxide previously carried on the support. It is usually 0.001 to 2 times by mol, preferably 0.005 to 1 times by mol, the amount of the basic metal oxide carried on the support.

[0108] Although many details remain unclear as to the mechanism by which the distribution of nickel and / or cobalt and the X component is achieved, it is presumed that the balance between the diffusion rate of nickel and / or cobalt and the X-containing soluble component in the carrier and the rate at which the component becomes insoluble through chemical reaction is well-balanced under the conditions of this embodiment, making it possible to fix the composite particles in a very narrow region near the surface of the carrier.

[0109] In addition, when an outer layer substantially not containing composite particles is formed on the outer surface of the carrier, aluminum is reacted with the basic metal component in the vicinity of the outer surface of the carrier to consume the basic metal component capable of reacting with nickel and / or cobalt and the X component in the vicinity of the outer surface of the carrier, and then nickel and / or cobalt and X are supported. Since the reactive basic metal component in the vicinity of the outer surface of the carrier has already been consumed, it is presumed that nickel and / or cobalt and X are immobilized by reacting with the basic metal oxide inside the carrier.

[0110] Next, the second step will be described. Prior to the heat treatment in the second step, the first precursor is washed with water and dried as necessary. The heating temperature of the first precursor is usually 40 to 900°C, preferably 80 to 800°C, more preferably 200 to 700°C, and further preferably 300 to 600°C.

[0111] The heat treatment is carried out in air (or atmospheric air), an oxidizing atmosphere (oxygen, ozone, nitrogen oxides, carbon dioxide, hydrogen peroxide, hypochlorous acid, inorganic / organic peroxides, etc.), or an inert gas atmosphere (helium, argon, nitrogen, etc.). The heating time may be appropriately selected depending on the heating temperature and the amount of the first precursor. The heat treatment may be carried out under normal pressure, elevated pressure, or reduced pressure.

[0112] After the second step described above, reduction treatment can be performed in a reducing atmosphere (hydrogen, hydrazine, formalin, formic acid, etc.) as necessary. In this case, a treatment method is selected that does not completely reduce the oxidized nickel and / or cobalt to the metallic state. The temperature and time of the reduction treatment can be appropriately selected depending on the type of reducing agent, the type of X, and the amount of catalyst.

[0113] Furthermore, after the above heat treatment or reduction treatment, an oxidation treatment can be carried out in air (or atmosphere) or in an oxidizing atmosphere (oxygen, ozone, nitrogen oxides, carbon dioxide, hydrogen peroxide, hypochlorous acid, inorganic or organic peroxides, etc.) as necessary. In this case, the temperature and time are appropriately selected depending on the type of oxidizing agent, the type of X, and the amount of catalyst.

[0114] The third component element other than nickel and / or cobalt and X can be added during preparation of the support or under reaction conditions. The alkali metal, alkaline earth metal, and rare earth metal can also be added during preparation of the catalyst or to the reaction system. The raw materials for the third component element, alkali metal, alkaline earth metal, and rare earth metal are selected from organic acid salts, inorganic acid salts, hydroxides, etc.

[0115] [Method of producing carboxylic acid ester] The catalyst for producing a carboxylate ester of the present embodiment can be widely used as a catalyst for chemical synthesis. For example, it can be used for a reaction for producing a carboxylate ester between an aldehyde and an alcohol, or for a reaction for producing a carboxylate ester from an alcohol. That is, the method for producing a carboxylate ester of the present embodiment can include a step of reacting (a) an aldehyde and an alcohol, or (b) one or more alcohols, in the presence of the catalyst for producing a carboxylate ester of the present embodiment and oxygen.

[0116] The catalyst for producing carboxylate esters of this embodiment exerts excellent effects, particularly when used as a catalyst for oxidation reactions. In addition to the aldehydes and alcohols used in the reactions for producing carboxylate esters shown in the examples, various reaction substrates, such as alkanes, olefins, alcohols, ketones, aldehydes, ethers, aromatic compounds, phenols, sulfur compounds, phosphorus compounds, oxygen-containing nitrogen compounds, amines, carbon monoxide, and water, can be used as reaction substrates. These reaction substrates can be used alone or as a mixture of two or more kinds. From these reaction substrates, various industrially useful oxygen-containing compounds and oxidation products such as oxidized adducts and oxidized dehydrogenates can be obtained.

[0117] Specific examples of reaction substrates include alkanes, such as aliphatic alkanes such as methane, ethane, propane, n-butane, isobutane, n-pentane, n-hexane, 2-methylpentane, and 3-methylpentane; and alicyclic alkanes such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane.

[0118] Examples of olefins include aliphatic olefins such as ethylene, propylene, butene, pentene, hexene, heptene, octene, decene, 3-methyl-1-butene, 2,3-dimethyl-1-butene, and allyl chloride; alicyclic olefins such as cyclopentene, cyclohexene, cycloheptene, cyclooctene, and cyclodecene; and aromatic substituted olefins such as styrene and α-methylstyrene.

[0119] Examples of the alcohol include saturated and unsaturated aliphatic alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, s-butanol, t-butanol, n-pentanol, n-hexanol, n-heptanol, allyl alcohol, and crotyl alcohol; saturated and unsaturated alicyclic alcohols such as cyclopentanol, cyclohexanol, cycloheptanol, methylcyclohexanol, and cyclohexen-1-ol; aliphatic and alicyclic polyhydric alcohols such as ethylene glycol, propylene glycol, trimethylene glycol, 1,3-butanediol, 1,2-cyclohexanediol, and 1,4-cyclohexanediol; and aromatic alcohols such as benzyl alcohol, salicylic alcohol, and benzhydrol.

[0120] Examples of aldehydes include aliphatic saturated aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, isobutyraldehyde, and glyoxal; aliphatic α,β-unsaturated aldehydes such as acrolein, methacrolein, and crotonaldehyde; aromatic aldehydes such as benzaldehyde, tolylaldehyde, benzylaldehyde, and phthalaldehyde, and derivatives of these aldehydes.

[0121] Examples of ketones include aliphatic ketones such as acetone, methyl ethyl ketone, diethyl ketone, dipropyl ketone, and methyl propyl ketone; alicyclic ketones such as cyclopentanone, cyclohexanone, cyclooctanone, 2-methylcyclohexanone, and 2-ethylcyclohexanone; and aromatic ketones such as acetophenone, propiophenone, and benzophenone.

[0122] Examples of aromatic compounds include benzene, toluene, xylene, naphthalene, anthracene, and derivatives thereof substituted with alkyl groups, aryl groups, halogens, sulfone groups, and the like.

[0123] Examples of phenols include phenol, cresol, xylenol, naphthol, anthol (hydroxyanthracene), and derivatives thereof (wherein the hydrogen atom of the aromatic ring is substituted with an alkyl group, an aryl group, a halogen atom, a sulfonic acid group, or the like).

[0124] Examples of the sulfur compounds include mercaptans such as methyl mercaptan, ethyl mercaptan, propyl mercaptan, benzyl mercaptan, and thiophenol.

[0125] Examples of the amines include aliphatic amines such as methylamine, ethylamine, propylamine, isopropylamine, butylamine, dimethylamine, diethylamine, dipropylamine, diisopropylamine, dibutylamine, trimethylamine, triethylamine, tripropylamine, tributylamine, allylamine, and diallylamine; alicyclic amines such as cyclopentylamine, cyclohexylamine, cycloheptylamine, and cyclooctylamine; and aromatic amines such as aniline, benzylamine, and toluidine.

[0126] These reaction substrates can be used alone or in the form of a mixture of two or more kinds. Moreover, they do not necessarily need to be purified, and may be used in the form of a mixture with other organic compounds.

[0127] Hereinafter, a method for producing a carboxylic acid ester by oxidative esterification reaction from an aldehyde and an alcohol in the presence of oxygen using the catalyst for producing a carboxylic acid ester of the present embodiment will be described as an example.

[0128] The aldehydes used as raw materials include, for example, C1-C aldehydes such as formaldehyde, acetaldehyde, propionaldehyde, isobutyraldehyde, and glyoxal. 10 Aliphatic saturated aldehydes; C3-C such as acrolein, methacrolein, and crotonaldehyde 10 Aliphatic α-β-unsaturated aldehydes; C6-C such as benzaldehyde, tolylaldehyde, benzylaldehyde, and phthalaldehyde 20Examples of the aldehyde include aromatic aldehydes and derivatives of these aldehydes. These aldehydes can be used alone or in a mixture of any two or more kinds. In this embodiment, the aldehyde is preferably selected from acrolein, methacrolein, or a mixture thereof.

[0129] Examples of alcohols include C1-C ethanol, isopropanol, butanol, 2-ethylhexanol, and octanol. 10 Aliphatic saturated alcohols; C5-C such as cyclopentanol and cyclohexanol 10 Alicyclic alcohols; C2-C such as ethylene glycol, propylene glycol, butanediol 10 Diols; C3-C such as allyl alcohol and methallyl alcohol 10 Aliphatic unsaturated alcohols; C6-C such as benzyl alcohol 20 Aromatic alcohols; hydroxyoxetanes such as 3-alkyl-3-hydroxymethyloxetane. These alcohols can be used alone or in any mixture of two or more. In this embodiment, the aldehyde is preferably acrolein and / or methacrolein, and the alcohol is preferably methanol.

[0130] The ratio of the amounts of aldehyde and alcohol is not particularly limited and can be in a wide range, for example, an aldehyde / alcohol molar ratio of 10 to 1 / 1,000, but is generally in the range of 1 / 2 to 1 / 50.

[0131] The amount of the catalyst used can vary significantly depending on the type of reaction raw materials, the composition and preparation method of the catalyst, the reaction conditions, the reaction format, etc., and is not particularly limited. However, when the catalyst is reacted in a slurry state, the catalyst is used so that the solid concentration in the slurry is preferably within the range of 1 to 50 mass / volume%, more preferably 3 to 30 mass / volume%, and even more preferably 10 to 25 mass / volume%.

[0132] The production of the carboxylic acid ester can be carried out by any method such as a gas phase reaction, a liquid phase reaction, or a flood reaction, either batchwise or continuously.

[0133] The reaction can be carried out without a solvent, but can also be carried out using a solvent inert to the reactants, such as hexane, decane, benzene, dioxane, and the like.

[0134] The reaction may be carried out in a conventional manner such as a fixed bed, a fluidized bed, a stirred tank, etc. For example, when the reaction is carried out in a liquid phase, any reactor type such as a bubble column reactor, a draft tube reactor, a stirred tank reactor, etc. may be used.

[0135] The oxygen used in the production of a carboxylate ester can be in the form of molecular oxygen, i.e., oxygen gas itself or a mixed gas obtained by diluting oxygen gas with a diluent inert to the reaction, such as nitrogen or carbon dioxide gas. From the viewpoints of operability, economy, etc., air is preferably used as the oxygen source.

[0136] The oxygen partial pressure varies depending on the reaction raw materials such as aldehyde species and alcohol species, the reaction conditions, the reactor type, etc., but in practice, the oxygen partial pressure at the reactor outlet is in a range where the concentration is below the lower limit of the explosion range, and is preferably controlled to, for example, 20 to 80 kPa. The reaction pressure can be carried out at any wide pressure range from reduced pressure to pressurized pressure, but is usually carried out at a pressure in the range of 0.05 to 2 MPa. In addition, from the viewpoint of safety, it is preferable to set the total pressure so that the oxygen concentration of the reactor outflow gas does not exceed the explosion limit (for example, oxygen concentration 8%).

[0137] When the reaction for producing a carboxylate ester is carried out in a liquid phase or the like, it is preferable to add a compound of an alkali metal or an alkaline earth metal (e.g., an oxide, hydroxide, carbonate, or carboxylate) to the reaction system to maintain the pH of the reaction system at 6 to 9. These compounds of alkali metals or alkaline earth metals can be used alone or in combination of two or more kinds.

[0138] The reaction temperature for producing a carboxylate ester can be as high as 200° C. or higher, but is preferably 30 to 200° C., more preferably 40 to 150° C., and further preferably 60 to 120° C. The reaction time is not particularly limited and cannot be uniquely determined since it varies depending on the conditions set, but is usually 1 to 20 hours. EXAMPLES

[0139] The present embodiment will be described more specifically below with reference to examples, but the present embodiment is not limited to these examples in any way.

[0140] In the following Examples and Comparative Examples, various physical properties were measured by the following methods.

[0141] [Viscosity measurement of mixed slurry] The viscosity of the mixed slurry was measured every hour from the start of stirring at room temperature under the following conditions. Viscometer: Brook Digital Viscometer "LVDV1M" Spindle: LV-1 Rotation speed: 100 rpm Temperature: Room temperature (25℃) The difference between the viscosity immediately before the start of feeding in the spray dryer and the viscosity one hour before the start of feeding was defined as the final Δviscosity.

[0142] [Determination of Ni and X loading amount and Ni / X atomic ratio] The concentrations of nickel and X in the composite particles were quantified using an IRIS Intrepid II XDL type ICP atomic emission spectrometer (ICP-AES, MS) manufactured by Thermo Fisher Scientific. The sample was prepared by weighing the support into a Teflon decomposition vessel, adding nitric acid and hydrogen fluoride, and decomposing by heating using a Milestone General ETHOS TC microwave decomposition apparatus. The mixture was then evaporated to dryness on a heater, and nitric acid and hydrochloric acid were added to the precipitated residue, which was then decomposed under pressure using the microwave decomposition apparatus. The decomposition liquid thus obtained was pure and of a constant volume, and used as the test liquid. The quantitative determination was performed by the internal standard method using ICP-AES, and the nickel and X contents in the catalyst were obtained by subtracting the blank value obtained at the same time, and the supported amount and atomic ratio were calculated.

[0143] [Analysis of the crystal structure of composite particles] The measurements were performed using a Rigaku Rint2500 powder X-ray diffractometer (XRD) with a Cu X-ray source (40 kV, 200 mA), a measurement range of 5 to 65 deg (0.02 deg / step), a measurement speed of 0.2 deg / min, and slit widths (scattering, diverging, receiving) of 1 deg, 1 deg, and 0.15 mm. The sample was uniformly spread on a non-reflective sample plate and fixed with neoprene rubber.

[0144] [Analysis of the chemical state of metal components in composite particles] The analysis was performed using a Thermo Electron ESCALAB250 X-ray photoelectron spectrometer (XPS) under the following conditions: excitation source AlKα 15 kV × 10 mA, analysis area approximately 1 mm (shape: ellipse), capture region: survey scan 0 to 1,100 eV, narrow scan Ni2p. The measurement sample was prepared by grinding the composite particle-supported material in an agate mortar, collecting it on a powder sample stage, and subjecting it to XPS measurement.

[0145] [Chemical state analysis of nickel] The NiKα spectrum was measured using a Technos XFRA190 double crystal high resolution X-ray fluorescence analyzer (HRXRF), and the various parameters obtained were compared with those of standard substances (nickel metal, nickel oxide) to infer the chemical state of nickel in the support, such as its valence. The measurement samples were used as they were. The Ni Kα spectrum was measured in partial spectrum mode. In this case, a Ge(220) crystal was used as the analyzing crystal, and the slit had a vertical divergence angle of 1°. The excitation voltage and current were set to 35 kV and 80 mA, respectively. In addition, filter paper was used as an absorber for the standard sample, and the counting time for the support sample was selected for each sample so that the peak intensity of the Kα spectrum was 3,000 cps or less and 10,000 counts or more. Measurements were repeated five times for each sample, and the metal sample was measured before and after the repeated measurements. After smoothing the measured spectrum (SG method 7 points - 5 times), the peak position, half-width (FWHM), and asymmetry coefficient (AI) were calculated, and the peak position was treated as the deviation from the measured value of the metal sample measured before and after the sample measurement, and the chemical shift (ΔE).

[0146] [Morphological observation and elemental analysis of composite particles] A JEOL 3100FEF transmission electron microscope / scanning transmission electron microscope (TEM / STEM) [accelerating voltage 300 kV, energy dispersive X-ray detector (EDX) attached] was used to measure TEM bright-field images, STEM dark-field images, and STEM-EDS compositional analysis (point analysis, mapping, line analysis). The data analysis software used was DigitalMicrographTM Ver.1.70.16, Gatan for TEM image and STEM image analysis (length measurement, Fourier transform analysis), and NORAN System SIX ver.2.0, Thermo Fisher Scientific for EDS data analysis (mapping image processing, quantitative composition calculation). The measurement sample was prepared by crushing the composite particle support in a mortar, dispersing it in ethanol, and ultrasonically cleaning it for about 1 minute. The resultant was then dropped and blown onto a Mo microgrid to prepare a sample for TEM / STEM observation.

[0147] [UV-Visible Spectroscopic Measurement of Composite Particles] The measurements were performed using a JASCO V-550 ultraviolet-visible spectrophotometer (UV-Vis) [integrating sphere unit, powder sample holder included] with a measurement range of 800-200 nm and a scanning speed of 400 nm / min. The measurement sample was prepared by grinding the composite particle-supported material in an agate mortar, placing it in a powder sample holder, and subjecting it to UV-Vis measurement.

[0148] [Observation of the shape of the support and catalyst for producing carboxylic acid esters] The carrier and the catalyst for producing a carboxylic acid ester were observed using a Hitachi X-650 scanning electron microscope (SEM).

[0149] [Catalyst for the production of carboxylic acid esters D 10 , D 50 , D 90 and half-width W] 0.2 g of catalyst was placed in a beaker, 16 mL of purified water was added, and then the catalyst was dispersed for 1 minute using a VCX130 ultrasonic disperser manufactured by SONIC & MATERIALS. INC. to prepare a measurement sample. This measurement sample was analyzed using a Beckman Coulter LS230 laser diffraction / scattering particle size distribution analyzer to determine the particle diameter D at which the cumulative frequency was x% in the volume-based particle size distribution of the catalyst for producing carboxylic acid esters. x (D 10 , D 50 , and D 90 ) and the half-width W of the particle size distribution (volume basis) were measured.

[0150] [Specific surface area] The specific surface area was measured by the BET method using Quadrasorb by Quantachrome Corporation.

[0151] [Measurement of bulk density (CBD) of catalyst for carboxylic acid ester production] As a pretreatment, about 120 g of the catalyst for producing carboxylic acid esters was collected in a stainless steel crucible and dried in a muffle furnace at 150°C for 6 hours. After calcination, the catalyst was placed in a desiccator (containing silica gel) and cooled to room temperature. Next, 100.0 g of the pretreated catalyst for producing carboxylic acid esters was collected and transferred to a 250 mL graduated cylinder, and the graduated cylinder was filled by tapping with a shaker for 15 minutes. After that, the surface of the sample in the graduated cylinder was flattened, and the filling volume was read. The bulk density was calculated by dividing the mass of the catalyst for producing carboxylic acid esters by the filling volume.

[0152] [Outflow rate] The outflow rate was calculated by the following formula based on the total amount of catalyst used in the production of a carboxylate ester described below and the amount of catalyst remaining after 500 hours of production of the carboxylate ester. Flow rate = {1-(amount of catalyst remaining / amount of catalyst used in reaction)} x 100 [%] Here, the residual catalyst amount was defined as the mass of the catalyst obtained by drying the catalyst for producing a carboxylic acid ester at 130° C. for 10 hours after carrying out the production of a carboxylic acid ester for 500 hours. That is, a catalyst with a high elution rate is likely to flow out of the reactor and is therefore unlikely to remain in the reactor, and as a result, less catalyst is available for reaction during long-term operation, which tends to result in a poor conversion rate.

[0153] [Example 1] (Production of catalyst for producing carboxylic acid ester) An aqueous solution of 3.75 kg of aluminum nitrate nonahydrate, 2.56 kg of magnesium nitrate, and 540 g of 60% nitric acid dissolved in 5.0 L of pure water was gradually added dropwise to 20.0 kg of silica sol solution (SiO2 content 30% by mass) with colloidal particle diameter of 10-20 nm in a stirred state maintained at 15°C, and the pH was adjusted to pH = 1.8. The raw material mixture (solid content 25% by mass) containing silica sol, aluminum nitrate, and magnesium nitrate obtained in this way was heated to 55°C. The raw material mixture was then stirred for 30 hours at a stirring impeller tip speed of 5.5 m / s, and a mixed slurry with a final Δviscosity of 0.5 mPa·s / Hr was obtained. Then, the feed amount / SD radius is 25×10 -3 [m 2 While feeding the slurry so that the slurry diameter was 1 / 100, the slurry was spray-dried at a disk (atomizer) peripheral speed of 80 m / s to obtain a solid. The SD radius refers to the horizontal radius of the rotating disk type spray dryer used in this example. The solid obtained was then packed in an open-top stainless steel container to a depth of about 1 cm, and heated from room temperature to 300°C over 2 hours in an electric furnace, after which it was held for 3 hours. The temperature was further raised to 600°C over 2 hours, held for 3 hours, and then slowly cooled to obtain a carrier. The obtained carrier contained 83.3 mol %, 8.3 mol %, and 8.3 mol % of silicon, aluminum, and magnesium, respectively, based on the total molar amount of silicon, aluminum, and magnesium. Furthermore, observation with a scanning electron microscope (SEM) showed that the shape of the carrier was almost spherical.

[0154] 300 g of the carrier obtained as described above was dispersed in 1.0 L of water heated to 90° C., and the mixture was stirred at 90° C. for 15 minutes. Next, an aqueous solution containing 16.35 g of nickel nitrate hexahydrate and 12 mL of a 1.3 mol / L aqueous solution of chloroauric acid was prepared, heated to 90° C., and added to the carrier slurry. Stirring was continued at 90° C. for an additional 30 minutes, and the nickel and gold components were insoluble and immobilized on the carrier. The mixture was then left to stand to remove the supernatant, washed several times with distilled water, and filtered. The mixture was dried in a dryer at 105°C for 10 hours, and then calcined in a muffle furnace in air at 450°C for 5 hours to obtain a catalyst for producing carboxylic acid esters (NiOAu / SiO2-Al2O3-MgO composite particle support) carrying 1.05% by mass of nickel and 0.91% by mass of gold. The Ni / Au atomic ratio of the obtained catalyst for producing carboxylic acid esters was 4.0. The composite particle support thus obtained was embedded in resin, polished, and the cross-section of the sample was subjected to line analysis using an X-ray microprobe (EPMA). As a result, it was confirmed that the support had an outer layer substantially free of nickel and gold in a region 0.5 μm deep from the outermost surface, nickel and gold were supported in a region up to a depth of 10 μm from the surface, and no composite particles were present inside the support. Next, the morphology of the composite particle support was observed with a transmission electron microscope (TEM / STEM), and it was confirmed that the support supported spherical nanoparticles with a maximum distribution of 2-3 nm particles (number average particle size: 3.0 nm). When the nanoparticles were further enlarged and observed, lattice fringes corresponding to the interplanar spacing of Au(111) were observed in the nanoparticles. When composition point analysis was performed on each nanoparticle using STEM-EDS, nickel and gold were detected in each particle. The average nickel / gold atomic ratio of the nanoparticles (calculated number: 50) was 1.05. Furthermore, when nano-area analysis was performed on the observed particles, the Ni / Au atomic ratio in the center of the particle was 0.90, and that in the particle edge was 2.56. Only a small amount of nickel was detected in the parts other than the particles. As a result of performing the same measurement at 50 points, nickel was detected in large amounts around the edge of each particle. From EDS element mapping, it was observed that the distribution of nickel and gold was almost the same. Furthermore, the composition line profile showed that nickel was distributed in a larger area than gold in both scanning directions. Powder X-ray diffraction (XRD) results showed that no diffraction pattern originating from nickel was observed, confirming that it exists in an amorphous state. However, although the peak was not clearly defined, a broad peak corresponding to gold crystals was present. Although this was close to the detection limit of powder X-ray diffraction (2 nm), the average crystallite diameter calculated using Scherrer's formula was approximately 3 nm. Regarding the chemical state of nickel, the results of X-ray photoelectron spectroscopy (XPS) confirmed that nickel was divalent. From the results of double crystal high resolution X-ray fluorescence spectrometry (HRXRF), the chemical state of nickel was estimated to be high spin divalent nickel, and the difference in the NiKα spectrum revealed that this was a different chemical state from nickel oxide, which is a single compound. The full width at half maximum (FWHM) of the NiKα spectrum of the catalyst obtained from the measured spectrum was 3.470, and the chemical shift (ΔE) was 0.335. The full width at half maximum (FWHM) of the NiKα spectrum of nickel oxide measured as a standard substance was 3.249, and the chemical shift (ΔE) was 0.344. In addition, when the change in the electronic excitation state of this composite particle support was investigated using ultraviolet-visible spectroscopy (UV-Vis), it was found that there was no surface plasmon absorption peak due to gold nanoparticles near 530 nm, but a broad absorption due to NiO2 was observed in the wavelength range of 200 to 800 nm. From the above results, it is inferred that the microstructure of the composite particles has a morphology in which the surfaces of gold nanoparticles are covered with oxidized nickel.

[0155] (Evaluation of the physical properties of catalysts for the production of carboxylic acid esters) The specific surface area of ​​the resulting catalyst for producing carboxylic acid esters was found to be 141 m 2 The particle size distribution of the catalyst for producing carboxylic acid esters was obtained by measuring the particle size distribution by a laser scattering method. The particle size distribution half width W was 50 μm, and D 50 , D 10 / D 50 , D 90 / D 50 , W / D 50 The particle size distribution was single peak. The bulk density was measured and was 1.05 g / cm. 3 It was.

[0156] (Production of Carboxylic Acid Esters) 240 g of the obtained catalyst for producing carboxylate ester was charged into a stirred stainless steel reactor equipped with a catalyst separator and having a liquid phase of 1.2 liters, and the reaction of producing oxidative carboxylate ester from aldehyde and alcohol was carried out while stirring the contents at a tip speed of 4 m / s. That is, a 36.7 mass% methacrolein / methanol solution was continuously fed to the reactor at 0.6 liters / hr and a 1-4 mass% NaOH / methanol solution was continuously fed to the reactor at 0.06 liters / hr, and air was blown in so that the outlet oxygen concentration was 8.0% by volume at a reaction temperature of 80°C and a reaction pressure of 0.5 MPa, and the NaOH concentration fed to the reactor was controlled so that the pH of the reaction system was 7. The reaction product was continuously extracted from the reactor outlet by overflow and analyzed by gas chromatography to examine the reactivity. 500 hours after the start of the reaction, the methacrolein conversion was 72%, the selectivity for methyl methacrylate was 95%, and the catalyst elution rate was 2%.

[0157] [Examples 2 to 7 and Comparative Examples 1 to 7] A catalyst for producing a carboxylate ester was produced in the same manner as in Example 1, except that the preparation conditions of the mixed slurry and the spray drying conditions in producing the carrier were changed as shown in Table 1. That is, (i) the solid content was adjusted by increasing or decreasing the amount of pure water in which aluminum nitrate nonahydrate and magnesium nitrate were dissolved in the raw material mixed liquid, and (ii) the pH was adjusted by increasing or decreasing the amount of 60 mass% nitric acid, so that they each became the values ​​in Table 1. The physical properties of the catalyst for producing a carboxylate ester were evaluated in the same manner as in Example 1, and further, a carboxylate ester was produced using the catalyst in the same manner as in Example 1, and the reaction results and the outflow rate of the catalyst were calculated. The particle size distribution based on volume of the catalysts in Examples 2 to 7 was a single peak. These results are shown in Table 1.

[0158] [Table 1]

Claims

1. A catalyst for producing a carboxylic acid ester, comprising catalytic metal particles and a support supporting the catalytic metal particles, The bulk density of the catalyst for producing a carboxylic acid ester is 0.50 g / cm 3 1.50g / cm or more 3 is as follows: The particle diameter at which the cumulative frequency is x% in the volume-based particle diameter distribution of the catalyst for producing a carboxylic acid ester is defined as D x When D 10 / D 50 ≧0.2 and D 90 / D 50 ≦2.5, When the half-width of the particle size distribution is W, W / D 50 ≦1.

5.

2. The catalyst for producing a carboxylic acid ester according to claim 1 , wherein W is 100 μm or less.

3. 3. The catalyst for producing a carboxylic acid ester according to claim 1 or 2, wherein the catalytic metal particles contain at least one element selected from the group consisting of nickel, cobalt, palladium, platinum, ruthenium, lead, gold, silver and copper.

4. The catalyst for producing a carboxylate ester according to any one of claims 1 to 3, wherein the catalytic metal particles are composite particles containing oxidized nickel and / or cobalt and X (X represents at least one element selected from the group consisting of nickel, palladium, platinum, ruthenium, gold, silver, and copper).

5. 5. The catalyst for producing a carboxylic acid ester according to claim 4, wherein a composition ratio of nickel or cobalt to X in the composite particle is 0.1 to 10 in terms of Ni / X atomic ratio or Co / X atomic ratio.

6. The catalyst for producing a carboxylic acid ester according to claim 4 or 5, wherein the composite particles contain nickel or cobalt in an oxidized state and gold.

7. The catalyst for producing a carboxylic acid ester according to any one of claims 4 to 6, wherein the composite particles have an average particle size of 2 to 10 nm.

8. The catalyst for producing a carboxylic acid ester according to any one of claims 4 to 7, wherein the support layer in which the composite particles are localized is present in a region from the surface of the catalyst for producing a carboxylic acid ester to 40% of an equivalent diameter of the catalyst for producing a carboxylic acid ester.

9. 9. The catalyst for producing a carboxylic acid ester according to claim 8, wherein the equivalent diameter is 200 μm or less, and the support layer in which the composite particles are localized is present in an area ranging from the surface of the catalyst for producing a carboxylic acid ester to 30% of the equivalent diameter of the catalyst for producing a carboxylic acid ester.

10. The catalyst for producing a carboxylic acid ester according to any one of claims 4 to 9, wherein the composite particle has a core made of X, and the core is coated with nickel or cobalt in an oxidized state.

11. The catalyst for producing a carboxylic acid ester according to any one of claims 1 to 10, wherein the support contains silica and alumina.

12. The above D 50 The catalyst for producing a carboxylic acid ester according to any one of claims 1 to 11, wherein the average particle diameter is 10 µm or more and 200 µm or less.

13. A method for producing a carboxylic acid ester, comprising a step of reacting (a) an aldehyde with an alcohol, or (b) one or more alcohols, in the presence of the catalyst for producing a carboxylic acid ester according to any one of claims 1 to 12 and oxygen.

14. The method for producing a carboxylic acid ester according to claim 13, wherein the aldehyde is acrolein and / or methacrolein.

15. The method for producing a carboxylic acid ester according to claim 13 or 14, wherein the aldehyde is acrolein and / or methacrolein, and the alcohol is methanol.

Citation Information

Patent Citations

  • Supported type oxidative esterification catalyst and preparation method and application thereof

    CN107519892A

  • Fluidized bed vinyl acetate catalyst

    JP2000176285A

  • Catalyst-coated support, method of production thereof, reactor containing same, and use thereof

    JP2008538323A

  • Direct and selective production of ethyl acetate from acetic acid using a binary metal-supported catalyst.

    JP2011529493A

  • Silica spherical particles and method for producing the same

    JP4420991B2